MIGRATORY GOSSYPIBOMA: AN UNUSUAL PRESENTATION OF A RARE SURGICAL COMPLICATION - Mansoor, Ali; Shaukat, Rabia; Saeed, Haroon; Chaudhary, Aamer Nadeem (Journal of Ayub Medical College Abbottabad, 2018)
Gossypiboma is a rare surgical complication associated with significant patient morbidity and even mortality. Migratory gossypiboma is a rarer subset of these cases, representing the erosion of surgical sponge into the intestine with consequent complications. A 40 years old female presented with a surgical sponge that had eroded into the caecum and subsequently moved with peristalsis up to the anal canal from which it was protruding out at the time of presentation. Proper checking before surgical closure can prevent this serious potentially life-threatening complication. Keywords: Gossypiboma; Retained surgical sponge; Intraluminal migration